2017
DOI: 10.1111/ejn.13536
|View full text |Cite
|
Sign up to set email alerts
|

Splenius capitis is a reliable target for measuring cervical vestibular evoked myogenic potentials in adults

Abstract: The cervical vestibular evoked myogenic potential (cVEMP) is a common and simple test of vestibulospinal reflex patency. In the clinic, cVEMPs are measured in response to loud sounds from the sternocleidomastoid (SCM) on the ventral neck, as subjects maintain an uncomfortable head posture needed to recruit SCM. Here we characterize the cVEMP in a dorsal neck turner (splenius capitis; SPL), and compare it with the SCM cVEMP. cVEMPs were recorded simultaneously via surface electromyography from SCM and SPL from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…As in cats and monkeys, human SCM also has a higher proportion of fast fibers and a more advantageous moment arm ( 104 106 ), leading us to predict that recruitment of this muscle related to vestibular reflexes would also be reserved for tasks requiring larger amounts of muscle force or particularly extreme postures. This line of thinking, as well related concerns about getting SCM to a sufficient level of contraction in a variety of postures, led us to investigate in humans whether cVEMPs could be recorded on one or both of ipsilateral-SCM and contralateral-SPL, relative to the side of the stimulated ear, in a head-turned posture ( 107 ) (Figure 6A ). This muscle pair acts synergistically for head turns and postures away from the side of the stimulated ear.…”
Section: Distribution Of Descending Commands In the Motor Peripherymentioning
confidence: 99%
See 1 more Smart Citation
“…As in cats and monkeys, human SCM also has a higher proportion of fast fibers and a more advantageous moment arm ( 104 106 ), leading us to predict that recruitment of this muscle related to vestibular reflexes would also be reserved for tasks requiring larger amounts of muscle force or particularly extreme postures. This line of thinking, as well related concerns about getting SCM to a sufficient level of contraction in a variety of postures, led us to investigate in humans whether cVEMPs could be recorded on one or both of ipsilateral-SCM and contralateral-SPL, relative to the side of the stimulated ear, in a head-turned posture ( 107 ) (Figure 6A ). This muscle pair acts synergistically for head turns and postures away from the side of the stimulated ear.…”
Section: Distribution Of Descending Commands In the Motor Peripherymentioning
confidence: 99%
“…Same format as Figure 1B . All parts of this figure take from data presented in Camp et al ( 107 ), with permission from Wiley and Sons.…”
Section: Distribution Of Descending Commands In the Motor Peripherymentioning
confidence: 99%
“…This inconsistency may be due to the fact that SC is located amongst other muscles with differing actions and vestibular projections. In contrast, Camp et al ( 41 ) and Rosengren et al ( 42 ) recorded motor unit responses from within the SC muscle and found short-latency inhibitory responses at 12–14 ms on the contralateral side. Thus stimulation of one ear with AC sound produced inhibition in the ipsilateral SCM and contralateral SC, allowing the agonist muscle pair to rotate the head toward the stimulated ear.…”
Section: Vemp-inspired Studies In Normal Volunteersmentioning
confidence: 95%
“…Open circles show reflexes whose polarity has either not been definitively determined (triceps and gastrocnemius) or is known to depend upon head position (soleus). Data are from: IO—Weber et al ( 39 ), masseter—Deriu et al ( 40 ), SCM—Colebatch et al ( 8 ), SC—Rosengren et al and Camp et al ( 41 , 42 ), triceps—Cherchi et al ( 43 ), gastrocnemius—Rudisill et al ( 44 ), soleus—Bacsi et al ( 45 ).…”
Section: Vemp-inspired Studies In Normal Volunteersmentioning
confidence: 99%
See 1 more Smart Citation